The effectiveness of spiritual deep breathing techniques on adolescent distress in orphanages in Rembang Central Java - Fitrio Devi Antony; Erti Ikhtiarini Dewi; Yeni Fitria; Enggal Hadi; Fitriani Fitriani (Alma Ata University Press, 2023)
Background: Adolescents who live in orphanages have various kinds of stressors such as adjustment to new environments, different backgrounds, academic stress, peer conflicts, financial problems, lack of affection, parental divorce, parents leaving family, and self-adjustment. The condition of adolescents who are unable to manage the stressors they face can make adolescents experience distress.Objectives: The study aims to analyze the effect of spiritual deep breathing teraphy on adolescents distress who lived in orphanages.Methods: This research used quasy experimental design method with pre-post test and control group design. The sample included 18 control groups and 18 treatmentgroup. The sampling technique use simple random sampling with mild, moderate, and severe distress and aged 13-18 years. Distress was measured using GHQ-12 (General Health Questionnaire-12) questionnaire and interventions which were given for 3 days with a duration of 10 minutes for each therapy. Data were analyzed by using both univariate and bivariate analysis with 95% (α = 0.05) significancy level.Results: The result showed majority of the rspondent who experienced severe distress (38.9%) and moderate distress (33.33%) were senior high school student. Result of T- Independen Test between post treatment group and post control group showed p=0,007 (p < 0.05), it means that there was a difference two groups.Conclusions: The result showed majority of the rspondent who experienced severe distress (38.9%) and moderate distress (33.33%) were senior high school student